Stereotactic Body Radiotherapy as Treatment for Organ Confined Low- and Intermediate-Risk Prostate Carcinoma, a 7-Year Study - Katz, Alan Jay; Kang, Josephine (Frontiers in Oncology, 2014)
Objectives: Stereotactic body radiation therapy (SBRT) takes advantage of the prostate’s low α/β ratio to deliver a large radiation dose in few fractions. Initial studies on small groups of low-risk patients support SBRT’s potential for clinical efficacy while limiting treatment-related morbidity and maintained quality of life. This prospective study expands upon prior studies to further evaluate SBRT efficacy for a large patient population with organ confined, low- and intermediate-risk prostate cancer patients. Methods: Four hundred seventy-seven patients with prostate cancer received CyberKnife SBRT. The median age was 68.6 years and the median PSA was 5.3 ng/mL. Three hundred twenty-four patients were low-risk (PSA <10 ng/mL and Gleason <7), 153 were intermediate-risk (PSA 10–20 ng/mL or Gleason = 7). Androgen deprivation therapy was administered to 51 patients for up to 6 months. One hundred fifty-four patients received 35 Gy delivered in five daily fractions; the remaining patients received a total dose of 36.25 Gy in five daily fractions. Biochemical failure was assessed using the phoenix criterion. Results: Median follow-up was 72 months. The median PSA at 7 years was 0.11 ng/mL. Biochemical failures occurred for 11 low-risk patients (2 locally), 14 intermediate-risk patients (3 locally). The actuarial 7-year freedom from biochemical failure was 95.6 and 89.6% for low- and intermediate-risk groups, respectively (p < 0.012). Among patients with intermediate-risk disease, those considered to have low intermediate-risk (Gleason 6 with PSA >10, or Gleason 3 + 4 with PSA <10; n = 106) had a significantly higher bDFS than patients with high intermediate-risk (Gleason 3 + 4 with PSA 10–20 or Gleason 4 + 3; n = 47), with bDFS of 93.5 vs. 79.3%, respectively. For the low-risk and low intermediate-risk groups, there was no difference in median PSA nadir or biochemical disease control between doses of 35 and 36.25 Gy. Conclusion: CyberKnife SBRT produces excellent biochemical control rates. Median PSA levels compare favorably with other radiation modalities and strongly suggest durability of response. These results also strongly suggest that 35 Gy is as effective as 36.25 Gy for low- and intermediate-risk patients.